Forest Diversity and Management 2006
DOI: 10.1007/978-1-4020-5208-8_23
|View full text |Cite
|
Sign up to set email alerts
|

Composition of woody species in a dynamic forest-woodland-savannah mosaic in Uganda: implications for conservation and management

Abstract: Abstract. Forest-woodland-savannah mosaics are a common feature in the East African landscape. For the conservation of the woody species that occur in such landscapes, the species patterns and the factors that maintain it need to be understood. We studied the woody species distribution in a forest-woodland-savannah mosaic in Budongo Forest Reserve, Uganda. The existing vegetation gradients were analyzed using data from a total of 591 plots of 400 or 500 m 2 each. Remotely sensed data was used to explore curren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 56 publications
2
18
0
Order By: Relevance
“…These numbers are slightly lower than our analysis of the circular plots where we observed an average of 668 trees 2-20 cm dbh/ ha, with and additional 100.7 trees >20 cm dbh/ha. In either case, this stand density is low compared to many dry tropical forest sites (Gentry, 1995;McLaren et al, 2005) but fits well within African savanna or open woodland classifications (White and Hood, 2004;Aerts et al, 2006;Nangendo et al, 2006). Examining patterns in the nearest neighbor analyses we found that adult trees are less spatially clumped than smaller trees (Fig.…”
Section: Spatial Pattern Within Plotssupporting
confidence: 55%
See 1 more Smart Citation
“…These numbers are slightly lower than our analysis of the circular plots where we observed an average of 668 trees 2-20 cm dbh/ ha, with and additional 100.7 trees >20 cm dbh/ha. In either case, this stand density is low compared to many dry tropical forest sites (Gentry, 1995;McLaren et al, 2005) but fits well within African savanna or open woodland classifications (White and Hood, 2004;Aerts et al, 2006;Nangendo et al, 2006). Examining patterns in the nearest neighbor analyses we found that adult trees are less spatially clumped than smaller trees (Fig.…”
Section: Spatial Pattern Within Plotssupporting
confidence: 55%
“…As a consequence, nearly 100% of the landscape, both inside and outside of protected areas is burned each year. This is a very high fire frequency for a dry tropical forest ecosystem and several recent studies have shown that the forest-woodland-grassland complex of much of central Africa is dependent on fire frequency and intensity (Nangendo et al, 2006). Our findings show evidence of such frequent burning with a tree size class structure indicative of continued recruitment within this system (i.e., far more small individuals than larger ones).…”
Section: Discussionmentioning
confidence: 56%
“…This species composition in turn influences the spectral reflectance of the vegetation in satellite images. In Nangendo et al (2006), this was observed to be the case in Budongo forest. The very open woodland and the wooded grassland classes occurred in sites that were recently burnt, and are probably burnt more often.…”
Section: Vegetation Cover Type Recognitionmentioning
confidence: 65%
“…For example, places with the exact same history of composition and configuration of biotic and abiotic components will likely evolve very differently if surrounded by mature forest versus urban development versus agriculture. This kind of neighborhood influence has been expressed as the manifestation of flows of material and energy (as in landscape ecology: [4]), the dispersal of propagules and competitive effects of neighbors (as in plant ecology: [59,60]), spatial autocorrelation (as in geography: [61,62]; as in ecology: [63]), and scale-dependent interconnectedness [37,64] and has been monitored both remotely [65] and with vegetation inventory data [66]. In land cover studies, remotely sensed imagery allows for wall-to-wall classification and mapping of broad areas [67].…”
Section: Landscape Dynamism and Spatial Contingencymentioning
confidence: 99%